The Role Of Islamic Economic System In Tackling Various Economic Issues - Telsy Fratama Dewi Samad (Maqrizi: Journal of Economics and Islamic Economics, 2021)
As a religion, Islam is not solely taught muslims how to worship Allah, perform Hajj, fulfill sunnah and Ramadhan fasting, etcetera. However, it also provides guidance through Al-Qur’an and sunnah how to deal with the life activity, in discourse, particularly economic matters. Nowadays, Islamic economic becomes one of economic systems in entire sphere, this paper aims to reveal the essential things concerning the role of Islamic economic system in fetching the goals of welfare economy. This paper used a qualitative method with a descriptive approach. The result found that by implementing the Islamic economic principles, accordingly the natural resources management will be far better than management nowadays, create equilibrium, boosting the empowerment economy nationally by the implementation of distributive just, prevent inequality and can be integrated in comprehensive economic system because each things regarding to the life of human being as well as to the science has been elucidated in Al-Qur’an and Sunnah which performed by Prophet Muhammad, as the foundation of Islamic economic thought that possess boarder insight encompass all economic aspects. It can be concluded that by the implementation of Islamic economic principles in managing the economy of society, accordingly will lead to welfare to humanity